A method for preparing a flow battery membrane material and applications thereof
Patent Information
- Application Number
- CN202211501130.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-11-28
AI Technical Summary
但是单纯的PP、PE、PET等材料制备的大孔径膜材料应用到液流电池中时,其电池效率较低,无法直接应用
[0051]本申请得到的膜材料机械强度高、制备方式灵活,制备的膜材料可以大幅度的提高全钒液流电池性能,降低膜材料成本,拓宽了全钒液流电池膜材料的使用范围。
Smart Images

Figure BDA0003967728460000061
Abstract
Description
Technical Field
[0001] This application relates to a method for preparing a flow battery membrane material and its application, belonging to the field of flow battery technology. Background Technology
[0002] Electrochemical energy storage is a rapidly developing type of energy storage in recent years. Flow battery energy storage has unique advantages such as high energy conversion efficiency, large storage capacity, flexible site selection, deep discharge capability, long battery life, safety and environmental protection. It is considered one of the most commercially promising energy storage batteries, especially suitable for application scenarios with long-term energy storage requirements.
[0003] In flow batteries, the separator is a crucial component, playing a vital role in battery performance and accounting for a significant proportion of battery cost. Therefore, developing low-cost, high-performance, and highly stable battery separators is an important step in the development of all-vanadium redox flow batteries.
[0004] Macroporous membrane materials made from materials such as PP, PE, and PET have attracted more attention due to their advantages such as good oxidation stability, good acid resistance, high mechanical properties, and low cost. However, when macroporous membrane materials made from materials such as PP, PE, and PET alone are used in flow batteries, their battery efficiency is low, making them unsuitable for direct application. Summary of the Invention
[0005] One aspect of this application provides a method for preparing a flow battery membrane material. The supporting layer of the membrane material provided by this invention is a macroporous base membrane with a pore size range of 10–100 μm. Because the selected base membrane is a micron-sized macroporous base membrane, when coating is directly applied to the surface of the base membrane, the coating solution will directly permeate from one side of the base membrane to the other side. Therefore, it is necessary to first fill the pores of the base membrane by using a water-soluble material as a pore filler to fill the pores and forming the membrane through solvent evaporation. Then, one or more layers of commonly used membrane-forming raw materials for flow batteries are coated on the filled base membrane material, and the solvent is removed by phase separation. Finally, water-soluble treatment is performed to remove the pore filler.
[0006] The preparation method includes:
[0007] (1) Coat the raw material liquid containing the pore-filling agent onto the first side surface of the base film, dry it, and obtain the filled base film material;
[0008] (2) Coating liquid containing coating material is applied to the second side surface of the base film to obtain a film material containing pore-filling agent;
[0009] (3) The membrane material containing the pore-filling agent is subjected to water-soluble treatment to obtain the flow battery membrane material.
[0010] Optionally, the pore-filling agent includes polyvinylpyrrolidone (PVP) and / or polyethylene glycol (PEG); the pore-filling agent is selected as a water-soluble material, and the pore-filling agent is used to fill the pores of the support layer base film;
[0011] The feed liquid containing the pore-filling agent has a dynamic viscosity of 900–30000 Pa·s at 25°C.
[0012] Optionally, the dynamic viscosity of the feed liquid containing the pore-filling agent at 25°C is 2000–20000 Pa·s.
[0013] Optionally, the dynamic viscosity of the feed liquid containing the pore-filling agent at 25°C is 5000-10000 Pa·s.
[0014] Optionally, the dynamic viscosity of the feed liquid containing the pore-filling agent at 25°C is independently selected from any value among 900 Pa·s, 2000 Pa·s, 4000 Pa·s, 5000 Pa·s, 6000 Pa·s, 8000 Pa·s, 10000 Pa·s, 15000 Pa·s, 20000 Pa·s, and 30000 Pa·s, or any range between any two of the above points.
[0015] Optionally, in step (1),
[0016] The coating thickness of the raw material solution containing the pore-filling agent on the first side surface of the base film is 10-100 μm;
[0017] Optionally, the drying temperature is 35–80°C.
[0018] Optionally, the coating thickness I of the raw material liquid containing the pore-filling agent on the first side surface of the base film is independently selected from any value among 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 80μm, and 100μm or any range between any two of the above.
[0019] Optionally, the drying temperature is independently selected from any value among 35°C, 50°C, 60°C, 70°C, and 80°C, or any range between any two of the above.
[0020] Optionally, the coating material is selected from at least one of polybenzimidazole (PBI), polyvinylidene fluoride (PVDF), polyether sulfone (PES), perfluorosulfonic acid resin (PFSA), and polystyrene (PS).
[0021] Optionally, in step (2),
[0022] The coating liquid containing coating material is coated on the second side surface of the base film with a thickness of 5 to 200 μm.
[0023] Optionally, the coating thickness II of the coating liquid containing the coating material on the second side surface of the base film is independently selected from any value among 5μm, 10μm, 15μm, 30μm, 50μm, 60μm, 80μm, 100μm, 120μm, 150μm, 180μm, and 200μm, or any range between any two of the above.
[0024] Optionally, the coating liquid containing the coating material has a mass concentration of 1-15% for the coating material.
[0025] Optionally, the mass concentration of the coating material is 3-12%.
[0026] Optionally, the mass concentration of the coating material is 5-8%.
[0027] Optionally, the mass concentration of the coating material is independently selected from any value of 1%, 3%, 5%, 6%, 8%, 10%, 12%, 15%, or any range between any two of the above.
[0028] Optionally, the base film is selected from at least one of polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET);
[0029] The pore size of the base film ranges from 10 μm to 100 μm;
[0030] The thickness of the base film is 20–1000 μm;
[0031] The porosity of the base membrane is 40-90%.
[0032] Optionally, the pore size range of the base film is independently selected from any value among 10μm, 20μm, 30μm, 50μm, 80μm, and 100μm, or any range between any two of the above points.
[0033] Optionally, the thickness of the base film is independently selected from any value among 20μm, 50μm, 100μm, 200μm, 400μm, 600μm, 700μm, 800μm, and 1000μm, or any range between any two of the above points.
[0034] Optionally, the porosity of the base membrane is independently selected from any value among 40%, 65%, 80%, and 90%, or any range between any two of the above points.
[0035] Optionally, the coating liquid further includes an organic solvent;
[0036] The organic solvent is selected from at least one of dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), and dimethyl sulfoxide (DMSO).
[0037] Optionally, step (2) further includes removing the organic solvent;
[0038] The method for removing organic solvents is selected from at least one of solvent evaporation phase separation, vapor reforming phase separation, and aqueous phase separation.
[0039] Solvent evaporation phase separation involves heating to evaporate the organic solvent and then forming a membrane, typically a dense membrane material. Steam reforming phase separation involves exchanging the organic solvent with water vapor, generally producing a porous membrane with a sponge-like pore structure. Aqueous phase separation involves exchanging the organic solvent with water, generally producing a porous membrane with a finger-like pore structure.
[0040] As one specific implementation method, the preparation method includes:
[0041] 1) Dissolve the water-soluble pore-filling material in water and mix thoroughly to obtain a homogeneous pore-filling raw material solution;
[0042] 2) Coat the obtained pore-filling agent raw material solution onto one side surface of the base film;
[0043] 3) Take out the diaphragm obtained in step 2), dry it, and obtain the base membrane material after filling;
[0044] 4) Dissolve the coating material in an organic solvent and mix thoroughly to obtain a homogeneous coating liquid;
[0045] 5) Apply the obtained homogeneous coating liquid to the surface of the base film material away from the filling layer;
[0046] 6) Remove the organic solvent from the membrane coated with the homogeneous coating obtained in step 5) by solvent evaporation phase separation to obtain a membrane material containing a pore-filling agent; dissolve the pore-filling agent by water immersion or water washing to obtain the desired flow battery membrane material.
[0047] Alternatively, the membrane coated with a homogeneous coating obtained in step 5) can be subjected to a steam reforming phase separation method to remove the organic solvent, and then subjected to water immersion treatment or water washing treatment to remove the pore filler, so as to obtain the desired flow battery membrane material.
[0048] Alternatively, the membrane coated with a homogeneous coating obtained in step 5) can be removed, and the organic solvent and pore filler can be removed by aqueous phase separation to obtain the desired flow battery membrane material.
[0049] Another aspect of this application is to provide a flow battery membrane material prepared by the above-described preparation method.
[0050] In another aspect of this application, the above-mentioned flow battery membrane material is provided as a separator in a flow battery.
[0051] The membrane material obtained in this application has high mechanical strength and flexible preparation method. The prepared membrane material can significantly improve the performance of vanadium redox flow batteries, reduce the cost of membrane materials, and broaden the application range of vanadium redox flow battery membrane materials.
[0052] The beneficial effects that this application can produce include:
[0053] 1. The method for preparing the diaphragm in this application is novel and rationally designed;
[0054] 2. The base membrane is selected as a large-pore material, and the base membrane material is widely available, simple to prepare, and low in material cost;
[0055] 3. The selected base membrane material has high mechanical strength, which improves the stability of the flow battery membrane material;
[0056] 4. By controlling the type and amount of composite raw materials, membrane materials with different properties can be obtained, which can be applied flexibly and in a wide range of fields.
[0057] 5. The film-making process of this application is simple and controllable, and suitable for large-scale production;
[0058] 6. This application broadens the scope of application of flow battery separators. Detailed Implementation
[0059] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0060] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.
[0061] Example 1
[0062] Taking a polyethylene membrane as an example (thickness 400 μm, average pore size 30 μm, porosity 65%) as the base membrane, polyvinylpyrrolidone (PVP) was selected as the pore filler, and dimethylacetamide was used as the solvent to prepare a homogeneous solution with a dynamic viscosity of 6000 Pa·s at 25°C. The dissolved PPVP homogeneous solution was coated onto one side of the prepared polyethylene membrane with a coating thickness of 20 μm, and dried at 50°C to obtain the desired filled base membrane material. For the coating material, perfluorosulfonic acid resin was selected, and dimethyl sulfoxide was used as the solvent with a mass concentration of 6%. The homogeneous coating liquid was coated onto the other side of the filled base membrane material away from the pore filler layer. At 50°C, the organic solvent was removed using a solvent evaporation phase separation method to obtain a membrane material containing the pore filler with a coating thickness of 30 μm. The membrane material containing the pore filler was then subjected to water immersion treatment to dissolve the pore filler, resulting in the desired flow battery membrane material.
[0063] The fabricated membrane material was tested using a vanadium redox flow battery. The catalyst layer was an activated carbon felt, the bipolar plates were graphite plates, and the effective area of the membrane was 48 cm². 2 60 mL of electrolyte for both positive and negative electrodes, with a vanadium ion concentration of 1.50 mol / L in the electrolyte. -1 The concentration of H2SO4 is 3 mol L. -1 At an operating current density of 80 mA / cm² -2 Under constant current charge and discharge conditions, the coulombic efficiency is 99% and the energy efficiency is 88.3%.
[0064] Examples 2-16
[0065] In Examples 2-16, the base film material, base film porosity, pore-filling agent selection, pore-filling agent coating selection, solvent selection, required flow battery membrane material preparation method, and battery testing conditions are all the same as in Example 1. The differences are shown in Table 1 below:
[0066] Table 1
[0067]
[0068] Comparative Example 1
[0069] Using a polyethylene membrane (400 μm thickness, 30 μm average pore size, 65% porosity) as the base membrane, a full vanadium redox flow battery test was directly performed. The process and conditions were the same as in Example 1, with an operating current density of 80 mA / cm². -2 Under constant current charging and discharging conditions, the experiment cannot be carried out if the aperture is too large.
[0070] Comparative Example 2
[0071] The battery testing process and conditions were the same as in Example 1, using a DuPont Nafion 115 film for testing, with an operating current density of 80 mA / cm².-2 Under constant current charge and discharge conditions, the coulombic efficiency is 95% and the energy efficiency is 83%.
[0072] Comparative Example 3
[0073] Taking a polyethylene membrane as an example (thickness 400 μm, average pore size 30 μm, porosity 65%) as the base membrane, polyvinylpyrrolidone (PVP) is selected as the pore filler, and dimethylacetamide is used as the solvent to prepare a homogeneous solution with a dynamic viscosity of 800 Pa·s at 25°C. The dissolved PPVP homogeneous solution is coated on one side of the prepared polyethylene membrane with a coating thickness of 20 μm and dried at 50°C to obtain the filled base membrane material. However, because the viscosity of the PPVP homogeneous solution is low, it permeates to the other side of the polyethylene membrane. The coating material was selected as perfluorosulfonic acid resin, and the solvent was dimethyl sulfoxide with a mass concentration of 6%. The homogeneous coating liquid was applied to the surface of the base film material away from the pore-filling agent layer after filling. Under the condition of 50 degrees Celsius, the organic solvent was removed by solvent evaporation phase separation method to obtain a membrane material containing pore-filling agent with a coating thickness of 30 μm. The membrane material containing pore-filling agent was then subjected to water immersion treatment to dissolve the pore-filling agent. Because the pore-filling agent has low viscosity, it was present on both sides of the base film. After water immersion treatment, the perfluorosulfonic acid resin also fell off along with the dissolution of the pore-filling agent, and the membrane material preparation failed.
[0074] Comparative Example 4
[0075] Taking a polyethylene membrane (400 μm thickness, 30 μm average pore size, 65% porosity) as an example, instead of pre-filling one side of the base membrane, perfluorosulfonic acid resin was directly coated onto one side of the base membrane using dimethyl sulfoxide as the solvent. The perfluorosulfonic acid resin had a mass concentration of 6% and a dynamic viscosity of 100 Pa·s at 25°C. The organic solvent was removed by solvent evaporation phase separation at 50°C, resulting in a coating thickness of 30 μm. Due to the low viscosity of the perfluorosulfonic acid resin solution, it directly penetrated to the other side of the base membrane. After film formation, both sides of the base membrane contained a perfluorosulfonic acid resin coating. Battery performance was tested using this membrane, with the testing process and conditions the same as in Example 1, and the operating current density was 80 mA / cm². -2 Under constant current charge and discharge conditions, the coulombic efficiency is 97% and the energy efficiency is 81%. It is evident that the presence of coatings on both sides increases the film resistance, leading to a decrease in the battery's energy efficiency.
[0076] Comparative Example 5
[0077] Taking a polyethylene membrane (400 μm thick, 30 μm average pore size, 65% porosity) as an example, instead of pre-filling one side of the base membrane, perfluorosulfonic acid resin was directly coated onto one side of the base membrane using dimethyl sulfoxide as the solvent. The perfluorosulfonic acid resin had a mass concentration of 30% and a dynamic viscosity of 5500 Pa·s at 25°C. The organic solvent was removed by solvent evaporation phase separation at 50°C, resulting in a coating thickness of 30 μm. Battery performance was tested using this membrane under the same procedures and conditions as in Example 1, with a working current density of 80 mA / cm². -2 Under constant current charge and discharge conditions, the coulombic efficiency was 98.6% and the energy efficiency was 81.3%. It is evident that the mass concentration of perfluorosulfonic acid resin also increases the membrane resistance, leading to a decrease in the battery's energy efficiency.
[0078] In summary, the flow battery membrane material provided in this application improves its efficiency in vanadium redox flow batteries. Because the base membrane uses large-pore materials such as PP, PE, and PET, the cost of the membrane material is effectively controlled. Furthermore, the membrane fabrication method is novel, the process is simple, and it is suitable for large-scale production. As shown in the example, when a polyethylene membrane (thickness 400 μm, average pore size 30 μm, porosity 65%) is selected as the base membrane, a homogeneous solution of polyvinylpyrrolidone (PVP) with a dynamic viscosity of 6000 Pa·s is prepared. The dissolved PPVP homogeneous solution is coated onto one side of the prepared polyethylene membrane with a coating thickness of 20 μm, and then dried at 50 degrees Celsius to obtain the desired filled base membrane material. The coating material is perfluorosulfonic acid resin, and the solvent is dimethyl sulfoxide with a mass concentration of 6%. The homogeneous coating liquid is applied to the surface of the base film material away from the pore-filling agent layer after filling. The organic solvent is removed by solvent evaporation phase separation method to obtain a membrane material containing pore-filling agent with a coating thickness of 30 μm. The membrane material containing pore-filling agent is then soaked in water to dissolve the pore-filling agent, and the desired flow battery membrane material is prepared. The membrane material with the highest efficiency is obtained in the vanadium redox flow battery test.
[0079] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a flow battery membrane material, characterized in that, (1) The raw material liquid containing the pore-filling agent is coated on the first side surface of the base film and dried to obtain the filled base film material; The pore-filling agent includes polyvinylpyrrolidone and / or polyethylene glycol; The raw material solution is coated only on the first side surface of the base film; The dynamic viscosity of the feed liquid containing the pore-filling agent at 25°C is 5000~10000 Pa·s; (2) A coating liquid containing coating material is applied to the second side surface of the base film to obtain a film material containing a pore-filling agent; The coating material is selected from at least one of polybenzimidazole, polyvinylidene fluoride, polyethersulfone resin, perfluorosulfonic acid resin, and polystyrene; The base film is selected from at least one of polypropylene, polyethylene, and polyethylene terephthalate; (3) The membrane material containing the pore filler is subjected to water-soluble treatment to remove the pore filler, thereby obtaining the flow battery membrane material.
2. The preparation method according to claim 1, characterized in that, In step (1), The coating thickness of the feed solution containing the pore-filling agent on the first side surface of the base film is 10~100µm; The drying temperature is 35~80℃.
3. The preparation method according to claim 1, characterized in that, In step (2), The coating liquid containing the coating material has a coating thickness of 5~200µm on the second side surface of the base film.
4. The preparation method according to claim 1, characterized in that, The coating liquid containing the coating material has a mass concentration of 1-15%.
5. The preparation method according to claim 1, characterized in that, The mass concentration of the coating material is 3-12%.
6. The preparation method according to claim 1, characterized in that, The mass concentration of the coating material is 5-8%.
7. The preparation method according to claim 1, characterized in that, The pore size of the base membrane ranges from 10µm to 100µm; The thickness of the base film is 20~1000µm; The porosity of the base membrane is 40-90%.
8. The preparation method according to claim 1, characterized in that, The coating liquid also includes organic solvents; The organic solvent is selected from at least one of dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and dimethyl sulfoxide.
9. The preparation method according to claim 8, characterized in that, Step (2) also includes removing the organic solvent; The method for removing organic solvents is selected from at least one of solvent evaporation phase separation, vapor reforming phase separation, and aqueous phase separation.
10. A flow battery membrane material prepared by the preparation method according to any one of claims 1 to 9.
11. The application of the flow battery membrane material of claim 10 as a separator in a flow battery.
Citation Information
Patent Citations
Diaphragm for full-vanadium ionic liquid flow battery, preparation method and battery comprising diaphragm
CN102005554A
Composite separator with multilayered structure and preparation method of separator
CN104362277A